Cross-Cultural Pragmatics: An Investigation into Speech Act Realization on The Ship - Limbong, Sunarlia; Palayukan, Novianty; Chandra, Ade; Jayanti, Retno Dwi; Riwu, Willyam Raimond (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study, titled "Cross-Cultural Pragmatics: An Investigation into Speech Act Realization on the Ship," aims to explore the influence of cultural backgrounds on the realization of speech acts among crew members in the Indonesian maritime industry. Specifically, it identifies the patterns and challenges associated with cross-cultural pragmatics on ships. Utilizing a descriptive qualitative design, the research was conducted on KM Lambelu, employing field notes, interviews, and observations as data collection instruments. The findings reveal that cultural backgrounds significantly influence how speech acts are realized by crew members, particularly regarding politeness, directness, and respect for hierarchy. The study highlights that while cultural diversity enriches interactions among crew members, it can also create communication barriers if not properly managed. The research further emphasizes that politeness strategies are deeply rooted in cultural norms, with a strong emphasis on seniority in hierarchical maritime settings.